KUALITAS LAYANAN VIA INSTAGRAM MARKETPLACE MEMBANGUN KEPUASAN CUSTOMER ZARA DI KOTA PADANG - Faiqah Nabila Prisca; Lucky Mahesa Yahya (Journal of Applied Management Studies, 2023)
This study aims to analyze the effect of product quality, price, and advertising on purchasing decisions of SMEs in Payakumbuh, using a case study of SMEs Sanjai Anna in Payakumbuh. This research was conducted by collecting data from 30 respondents who are customers of UMKM Sanjai Anna. The data collection method was carried out by distributing questionnaires to respondents who were selected purposively. The questionnaire consists of questions related to product quality, price, advertising, and purchasing decisions. The collected data were then analyzed using multiple linear regression techniques and hypothesis testing. The results of the study show that product quality, price, and advertising have a significant effect on purchasing decisions at Sanjai Anna's SMEs. Good product quality can increase customer confidence and satisfaction with the product, thereby influencing purchasing decisions. Competitive prices and promotion through advertising also have a positive influence on purchasing decisions. This research makes an important contribution to the understanding of the factors that influence purchasing decisions for MSMEs in Payakumbuh, especially for Sanjai Anna's MSMEs. The results of this study are expected to provide input for MSME owners in developing marketing strategies